MACROECONOMICS OF TAXATION AND ECONOMIC GROWTH IN NIGERIA - Aniefor, Jone Sunday; Orife, Catherine Ogheneovo (Journal of the Management Sciences, 2023)
The study empirically examined the macroeconomic impact of taxation on economic growth in Nigeria. The main objectives of the study are to examine the impact of VAT on economic growth in Nigeria. Investigate the impact of petroleum profit tax on the economic growth of Nigeria. The method of data collection was derived from secondary, certified sources; namely the National Bureau of Statistics, Central Bank of Nigeria and Federal Domestic Revenue Report 2000-2021. The data were analyzed using a regression model to determine the relationship between the dependent variables. The study used an econometric approach to estimate the relationship between taxation and economic growth. The ordinary least squares (OLS) technique was used to obtain numerical estimates of the coefficients of the various equations. The results of the study show that value added tax (VAT) has a significant positive effect on economic growth, while petroleum profit tax (PPT) has a significant negative effect. It was recommended that Nigerian government should continue to implement VAT because it has a significant positive impact on economic growth.